Deskripsi dan Preferensi Pohon Sarang Tarsius (Tarsius supriatnai) di Suaka Margasatwa Nantu Gorontalo - Repi, Terri (Universitas Gadjah Mada, 2024)
Tarsiers (Tarsius supriatnai) were part of the endemic primates in Sulawesi categorized as vulnerable in the IUCN red list. Therefore, this research aimed to describe and analyze the characteristics, preferences, and determinant factors influencing the use of nest trees by tarsiers in Nantu Wildlife Reserve, Gorontalo. This research used a direct observation method to collect data for three months, from September to November 2013, focusing on temperature, humidity, light intensity, tree height, tree diameter, nest height from the ground, and frequency of nest use. Moreovr, the Neu index was applied to determine nest preferences and multiple linear regression analysis was used to analyze the factors influencing nest tree selection. The results showed that the primates preferred eight nest trees, including Ficus altissima (w=1.58) and Ficus benjamina (w=1.50). Multiple linear regression analysis showed that the humidity (4.103±3.674%, P>0.05) and light intensity (126.362±41.149 lx, P<0.05) became dominant factors influencing the frequency of nest use. The results generally showed that vegetation species and microclimate conditions were crucial for tarsiers, indicating the importance of preserving forest areas to ensure the conservation of these primates.